2018
DOI: 10.1186/s13256-018-1832-7
|View full text |Cite
|
Sign up to set email alerts
|

High-flow oxygen via tracheostomy facilitates weaning from prolonged mechanical ventilation in patients with restrictive pulmonary dysfunction: two case reports

Abstract: BackgroundWeaning from prolonged mechanical ventilation is extremely difficult in tracheostomized patients with restrictive pulmonary dysfunction. High-flow oxygen via tracheostomy supplies heated and humidified oxygen gas at > 10 L/minute. However, little has been reported on the use of high-flow oxygen via tracheostomy during weaning from ventilators in patients with restrictive pulmonary dysfunction. We report successful weaning from ventilators in patients with restrictive pulmonary dysfunction using high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 7 publications
1
12
0
7
Order By: Relevance
“…Our experiment showed that HFT generates approximately 0.3, 0.5, and 0.9 cmH 2 O of pPEEP with flows of 40 L/min, 50 L/min, and 60 L/min, respectively. The magnitude of these measures corresponds reasonably with previous studies of airway pressure in previous studies [ 13 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our experiment showed that HFT generates approximately 0.3, 0.5, and 0.9 cmH 2 O of pPEEP with flows of 40 L/min, 50 L/min, and 60 L/min, respectively. The magnitude of these measures corresponds reasonably with previous studies of airway pressure in previous studies [ 13 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Evidence for improved CO 2 clearance with HFT is limited to the Mitaka case report. The authors suggest the presence of restrictive lung disease may have played a role [ 15 ]. Whether HFT offers an advantage for restrictive lung pathology where any dead space washout is likely to be proportionally greater may be explored in future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mitaka et al reported successful weaning of two PMV patients with restrictive pulmonary function. 16 He observed that high inspiratory oxygen flow facilitates weaning by enhancing tidal volume and reducing their inspiratory efforts and work of breathing. He further suggested that in contrast to their study, Corley et al, failed to exhibit an increase in EELV as their patients were more generalized and lacked any restrictive pulmonary dysfunction.…”
Section: Discussionsmentioning
confidence: 99%
“…HFT provides superior optimal humidification than does COT, which supplies cold and dry oxygen flow. Mitaka et al presented two cases report demonstrating that HFT facilitates weaning from prolonged mechanical ventilation (PMV) in patients with restrictive lung disease [16]. Few studies have compared HFT and COT with respect to clinical performance (Table 1).…”
Section: Hft Vs Cotmentioning
confidence: 99%